MISTERI BUNDA MARIA DIANGKAT KE SURGA: Suatu Pencarian Makna Iman - Balela, Yoseph Solor (LOGOS, 2008)
In 1950, Pope Pius XII, in the apostolic constitution Munificentissimus Deus, promulgated the Assumption of the Blessed Virgin Mary as a dogma of the Church. It was declared that the Immaculate Mother of God, Mary ever virgin, having completed the course of her earthly life, was assumed body and soul to heavenly glory. An assumption is an act of God. She was taken up by the power of God. The glorification of Mary was following the ascension of Jesus Christ, her son. It seems impossible that she who so much loved him should after the earthly life be separated from him in either body or soul. The assumption of Mary is the first fruit of his own glorification. However the dogma is still opened regarding whether or not she actually died. The faithful believe that she had been transformed from the earthly body to the heavenly body. She had been glorified in her total human personhood. The glorious assumption of Mary is also a sign of the glorious assumption of the whole Church. We behold in her glorification a sign of certain hope and comfort for the whole Church, as well as for her individual members. When we celebrate the Assumption of Mary, we are celebrating our own final glory. Through “the woman clothed with the sun”, we receive a special blessing to be light for others.